Pengaruh Service Qualiy Dan Facilities Terhadap Keputusan Pembelian Melalui Minat Beli Sebagai Variabel Intervening (Studi Kasus Pada Pengguna Jasa Trans Jogja di Kota Yogyakarta) - Ismi Rumiyati; Henny Welsa; Nonik Kusuma Ningrum (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine how much influence Service Quality and Facilities have on Purchase Decisions through Purchase Interest as an Intervening Variable (Case Study on Trans Jogja). The population used in this study are consumers who have used Trans Jogja services. The sample in this study was 84 respondents using the Non-Probability Sampling technique with a purposive sampling approach, taking samples based on certain criteria, with respondents who had used Trans Jogja services. This data was taken using a questionnaire via google form, after the questionnaire results were collected, the data was tabulated using MS Excel and analyzed using SPSS version 23. The results of this study indicate that Service Quality and Facilities have a positive and significant effect on Purchase Interest. Service Quality has a positive and significant effect on Purchase Decisions. Facilities have a positive and insignificant effect on Purchase Decisions. Buying Interest has a positive and significant effect on Purchase Decisions. The influence of Service Quality on Purchase Decisions through Purchase Interest as an intervening variable is accepted. Influence of Facilities on Purchase Decision through Purchase Interest as an accepted intervening variable. Keywords: Service Quality; Facilities ; Buying decision ; Buying Interest